2012
DOI: 10.1016/j.jvs.2011.09.098
|View full text |Cite
|
Sign up to set email alerts
|

A fresh cadaver laboratory to conceptualize troublesome anatomic relationships in vascular surgery

Abstract: Fresh cadaver laboratories can provide a learner-centered and safe environment for acquiring procedural understanding and operative confidence of complex vascular exposures. This may allow for the transformational change essential to becoming a competent vascular surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 19 publications
0
42
1
1
Order By: Relevance
“…This technique is still used, and its benefits to surgical training have been reported in vascular surgery, plastic surgery, and gynecology. [12][13][14][15][16][17] Despite the obvious benefits of fresh tissue dissection, all past applications have lacked physiologic parameters of blood flow and pressure.…”
mentioning
confidence: 99%
“…This technique is still used, and its benefits to surgical training have been reported in vascular surgery, plastic surgery, and gynecology. [12][13][14][15][16][17] Despite the obvious benefits of fresh tissue dissection, all past applications have lacked physiologic parameters of blood flow and pressure.…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15][16][26][27][28][29][30][31][32] However, none of those measures are specific for trauma-related emergency surgical procedures, which have unique temporal and management criteria, nor is individual surgeon performance measured systematically or specifically during residency training. 32 The present study of trauma-specific vascular procedures shows that correct identification of surface landmarks, incisions, and procedural steps can be documented and the IPS increased for vascular exposure and control after ASSET training.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, cadaveric simulation was employed within a curriculum; therefore, it is unsure whether the effect on trainees' confidence was due to the hands-on practice or the remaining aspects of the curriculum. Mitchell et al [17] used fresh frozen cadavers to teach dissection of structures rarely identified in vascular surgery and showed increased post-simulation anatomical knowledge and confidence. Transferability of skills to the real operating theatre was not assessed.…”
Section: Comparatorsmentioning
confidence: 99%